2001
DOI: 10.1074/jbc.m106702200
|View full text |Cite
|
Sign up to set email alerts
|

The Stereoselective Targeting of a Specific Enzyme-Substrate Complex Is the Molecular Mechanism for the Synergic Inhibition of HIV-1 Reverse Transcriptase by (R)-(−)-PPO464

Abstract: The human immunodeficiency virus type 1 (HIV-1) nonnucleoside reverse transcriptase (RT) inhibitor pyrrolopyridooxazepinone (PPO) derivative, (؎)-PPO294, was shown to be active toward wild type and mutated HIV-1 RT and to act synergistically in combination with 3-azido-3-deoxythymidine (Campiani, G., Morelli, E., Fabbrini, M., Nacci, V., Greco, G., Novellino, E., Ramunno, A., Maga, G., Spadari, S., Caliendo, G., Bergamini, A., Faggioli, E., Uccella, I., Bolacchi, F., Marini, S., (1999) J. Med. Chem. 42, 4462-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 32 publications
3
16
0
Order By: Relevance
“…Previous observations indicated that the inhibition of HIV-1 RT by the NNRTI PPO464 was due to the specific binding of this molecule to the ternary complex formed by RT, the template primer, and the dNTP (25). In the present study we extended the analysis to molecules belonging to a related class of NNRTIs, the PBO derivatives, whose structures are shown in Fig.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Previous observations indicated that the inhibition of HIV-1 RT by the NNRTI PPO464 was due to the specific binding of this molecule to the ternary complex formed by RT, the template primer, and the dNTP (25). In the present study we extended the analysis to molecules belonging to a related class of NNRTIs, the PBO derivatives, whose structures are shown in Fig.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, we have shown that the lead compound of this class, (R)-(Ϫ)-PPO464, was selectively targeting the ternary complex formed by the viral RT with its substrates nucleic acid and nucleotide. It showed a significant synergy with the NRTI zidovudine and a favorable pharmacokinetic profile in mice and rats, either alone or during coadministration with the HIV-1 PI ritonavir (25). The results of the biological and pharmacokinetic experiments suggest a potential clinical utility of PBO and PPO analogs in combination with NRTIs against strains of HIV-1 bearing mutations that confer resistance to known NNRTIs.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…This means that, in principle, the NNBS might not be identical in these three mechanistic forms. Several kinetic studies have shown that this is indeed the case, so that some NNRTIs selectively target one or a few of the different enzymatic forms along the reaction pathway (5,13,15). This observation likely reflects the different spatial rearrangements not only of the NNBS itself but also of the adjacent nucleotide binding site (3,20,26,27).…”
mentioning
confidence: 98%
“…The ethyl ester of N-{3-[ (3,5- Nucleic acid substrates. The homopolymer poly(rA) (Pharmacia) was mixed at weight ratios in nucleotides of 10:1 to the oligomer oligo(dT) [12][13][14][15][16][17][18] (Pharmacia) in 20 mM Tris-HCl (pH 8.0) containing 20 mM KCl and 1 mM EDTA, heated at 65°C for 5 min, and then slowly cooled at room temperature.…”
Section: Chemicals [mentioning
confidence: 99%